Roadmap “Gestão ESG&Construção Civil” : objetivos estratégicos ambientais, sociais e de governança para empresas do subsetor de edificações em Mato Grosso - Ferreira, Luciana Maria de Almeida e Silva (2024)
Civil construction is considered a polluting industry, with a high environmental impact, despite generating a high number of jobs and receiving a large amount of investments. Therefore, it has high adherence to the ESG (Environmental, Social and Governance) agenda and Environmental, Social and Governance, in Portuguese. However, the sector still faces difficulties in absorbing and structuring initiatives related to this theme, and it is verified that there is a gap in the learning system to accelerate the paradigm shift on sustainability. In view of this, the objective of the research was to prepare a roadmap ESG MANAGEMENT & CIVIL CONSTRUCTION, following the methodological route based on the triangulation strategy, by associating knowledge from the areas of Architecture, Engineering and Construction (AEC), Public Policies and Administration to identify structuring actions of a strategic nature, aiming to boost the implementation of ESG-based management in the Civil Construction industry in Mato Grosso, Buildings subsector. The roadmap was outlined with information from the stages of: i) survey and analysis of the legislation, ii) definition of ESG actions adhering to the life cycle of the building (asset), iii) opinion surveys of key actors through an electronic form; and, iv) validation was carried out by a panel of experts. The roadmap was graphically represented, with the ESG objectives constituting a multi-layered journey, highlighting the complexity of implementation, relating the main Sustainable Development Goals and predicting implementation milestones. The results highlight the need for awareness and involvement of senior management to guide the ESG culture, with governance being the structuring link between the social and environmental pillars. Social actions, with regard to labor responsibility and safety at work, are already provided for in public policies and regulatory standards, and are mandatory for the sector to comply with, and should not be characterized as ESG actions, since they precede them. As social and environmental commitment and compliance actions are incorporated, it is identified that there is an evolution in ESG maturity because systemic approaches and reformulation of the organizational structure are necessary. Finally, some actions, such as the implementation of a quality management system and the treatment and proper disposal of effluents at the construction site, are considered complex in terms of practical implementation, but are considered a priority. Research, development and innovation fit as a support to facilitate the paradigm shift, but they are still little implemented, either due to ignorance of their potential results or the need to invest financial resources.